Pemahaman Hukum Waris Islam dan Kemampuan Mahasiswa dalam Menyelesaikan Soal Pembagian Warisan - Nur Asyiah Siregar; Hotni Sari Harahap (HIBRUL ULAMA, 2025)
This study aims to analyze the effect of understanding the legal basis of Islamic inheritance law (X1) and understanding the principles of ashab al-furudh and asobah (X2) on students' ability to solve inheritance division problems (Y). The research uses an associative quantitative approach with a sample of 170 students from the Islamic Education Program at the University of Al-Washliyah Medan, from the 5th and 7th semesters. The sample was determined using the Slovin formula and stratified random sampling technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, normality tests, Pearson correlation, and multiple linear regression with the help of SPSS version 24. The results show that the instruments are valid and reliable, and the data is normally distributed. Simultaneously, X1 and X2 significantly influence Y (F = 208.724; sig. < 0.001) with an R² of 0.714. Partially, X1 has a positive and significant effect, while X2 has the most dominant influence. In conclusion, both normative and technical understanding are equally important in enhancing students' ability to solve faraid problems.